Insulin Resistance Increases MRI-Estimated Pancreatic Fat in Nonalcoholic Fatty Liver Disease and Normal Controls. (17th November 2013) - Patel, Niraj S.; Peterson, Michael R.; Lin, Grace Y.; Feldstein, Ariel; Schnabl, Bernd; Bettencourt, Ricki; Seki, Ekihiro; Sirlin, Claude B.; Loomba, Rohit
Abstract : Background . Ectopic fat deposition in the pancreas and its relationship with hepatic steatosis and insulin resistance have not been compared between patients with nonalcoholic fatty liver disease (NAFLD) and healthy controls. Aim . Using a novel magnetic resonance imaging (MRI) based biomarker, the proton-density-fat-fraction (MRI-PDFF), we compared pancreatic fat content in patients with biopsy-proven NAFLD to healthy controls and determined whether it is associated with insulin resistance and liver fat content. Methods . This nested case-control study was derived from two prospective studies including 43 patients with biopsy-proven NAFLD and 49 healthy controls who underwent biochemical testing and MRI. Results . Compared to healthy controls, patients with NAFLD had significantly higher pancreatic MRI-PDFF (3.6% versus 8.5%, P value <0.001), and these results remained consistent in multivariable-adjusted models including age, sex, body mass index, and diabetes (P value =0.03). We found a strong correlation between hepatic and pancreatic MRI-PDFF (Spearman correlation, P = 0.57, P value <0.001). Participants with increased insulin resistance determined by homeostatic-model-of-insulin-resistance (HOMA-IR) greater than 2.5 had higher pancreatic (7.3% versus 4.5%, P value =0.015) and liver (13.5% versus 4.0%, P value <0.001) MRI-PDFF. Conclusion . Patients with NAFLD have greater pancreatic fat than normal controls. Insulin resistance is associated with liver and pancreatic fat accumulation.